Core decompression and autologous bone marrow concentrate for treatment of femoral head osteonecrosis: a randomized prospective study - Pepke, Wojciech; Kasten, Philip; Beckmann, Nicholas A.; Janicki, Patricia; Egermann, Marcus (Orthopedic Reviews, 2016)
The aim of this study was to investigate the safety of injection of bone marrow aspirate concentrate during core decompression and to study its clinical (visual analogue scale; Harris-Hip-score) and radiological outcomes (magnetic resonance imaging). In this prospective and randomized clinical trial we evaluated 24 consecutive patients with nontraumatic femoral head necrosis (FHN) during a period of two years after intervention. In vitro analysis of mesenchymal stem cells was performed by evaluating the fibroblast colony forming units (CFU-Fs). Postoperatively, significant decrease in pain associated with a functional benefit lasting was observed. However, there was no difference in the clinical outcome between the two study groups. Over the period of two years there was no significant difference between the head survival rate between both groups. In contrast to that, we could not perceive any significant change in the volume of FHN in both treatment groups related to the longitudinal course after treating. The number of CFU showed a significant increase after centrifugation. This trial could not detect a benefit from the additional injection of bone marrow concentrate with regard to bone regeneration and clinical outcome in the short term.